Social skills training and play group intervention for children with oppositional-defiant disorders/conduct disorder: Mediating mechanisms in a head-to-head comparison. (30th September 2019) - Katzmann, Josepha; Goertz-Dorten, Anja; Hautmann, Christopher; Doepfner, Manfred
Abstract: Objective : Social-cognitive information processing, social skills, and social interactions are problem-maintaining variables for aggressive behavior in children. We hypothesized that these factors may be possible mediators of the mechanism of change in the child-centered treatment of conduct disorders (CDs). The aim of the present study (Clinical trials.gov Identifier: NCT01406067) was to examine putative mechanisms of change for the decrease in oppositional-defiant behavior resulting from child-centered treatment of patients with oppositional-defiant disorder (ODD) or CD. Method : 91 children (age 6–12 years) with ODD/CD were randomized to receive either social skills training or to a resource activating play group. Mediator analyses were conducted using path analyses. Results : The assumed mediating effects were not significant. However, alternative models with the putative mediators and outcome in reversed positions showed significant indirect effects of the oppositional-defiant symptoms as mediator for the decrease of disturbance of social-information processing, social skills, and social interactions. Conclusions : The proposed model for mechanisms of change could not be confirmed, with the results pointing to a reversed causality. Variables other than those hypothesized must be responsible for mediating the effects of the intervention on child oppositional-defiant behavior. Possible mechanisms of change were discussed.